PENGARUH STRUKTUR MODAL DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN PADA PT KALBE FARMA TBK PERIODE 2015-2024 - Sulisti, Vera; Safii, Mohamad (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
This study aims to determine the Influence of Capital Structure (DER) and Profitability (ROA) on Company Value (PBV) at PT Kalbe Farma Tbk for the 2015-2024 Period. The data used is secondary data in the form of financial statements of PT Kalbe Farma Tbk obtained from the official website of PT Kalbe Farma Tbk which is listed on the Indonesia Stock Exchange. In this study, the researcher used a quantitative method by testing hypotheses with statistical methods using the Statistical Package for the Social Sciences (SPSS) application program version 25. The data analysis techniques used were descriptive statistical tests, classical assumption tests, multiple linear regression, hypothesis tests, correlation coefficients and determination coefficients. The results of the study show that partially, the Capital Structure (DER) does not have a significant negative influence on the Company Value (PBV) with a calculation of │-458 │< table of 2.365 and a significance value of 0.661 > 0.05. Profitability (ROA) had a significant positive effect on the Company Value (PBV) with a calculation of 6.026 > table 2.365 with a significance level of 0.001 < 0.05. The results of the simultaneous test showed that Capital Structure (DER) and Profitability (ROA) had a significant positive effect on the Company Value (PBV) with a value of Fcal 22.019 > Ftable of 4.74 and a significance value of 0.001< 0.05. The coefficient of determination (R²) value of 0.824 indicates that Debt to Equity Ratio and Return on Assets contribute 82.4% to the Price to Book Value, while the remaining 17.6% is influenced by other variables not examined in this study.